2014
DOI: 10.3945/jn.114.193664
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Breastfeeding Is Inversely Associated with Risk of Childhood Overweight in a Large Chinese Cohort

Abstract: The association between breastfeeding status and childhood overweight is inconclusive. The aim of the present study was to investigate the relation between exclusive breastfeeding and childhood overweight risk in children 4-5 y of age in Southeast China. Among 97,424 children enrolled between 1999 and 2009 in the Jiaxing Birth Cohort, 42,550 of them were included in the final analysis with complete records on breastfeeding status and anthropometric measurements at 4-5 y of age (48-60 mo). Overweight and being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
2
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 30 publications
2
37
2
6
Order By: Relevance
“…The factors associated with a greater prevalence of overweight were the child not breastfeeding at six months and the absence of paid maternal employment. This result corroborates the conclusions of previous studies in which breastfed infants had a lower likelihood of being obese 11,17 . However, this finding differs to the results of other studies concluding that infant overweight was associated with maternal employment outside the home 14,18 .…”
Section: Variablessupporting
confidence: 92%
“…The factors associated with a greater prevalence of overweight were the child not breastfeeding at six months and the absence of paid maternal employment. This result corroborates the conclusions of previous studies in which breastfed infants had a lower likelihood of being obese 11,17 . However, this finding differs to the results of other studies concluding that infant overweight was associated with maternal employment outside the home 14,18 .…”
Section: Variablessupporting
confidence: 92%
“…Sex specificity has been reported for other obesogenic exposures in early life, with males being disproportionately affected by maternal smoking, 38 antibiotic exposure, 39,40 and formula feeding. 41 This sexual dimorphism may be related to sex differences in gut microbiota, 42 which contribute to host metabolism and weight gain. 43 Our findings may support this intriguing hypothesis because NNSs have been shown to modify gut microbiota, 15 although this has not yet been demonstrated for prenatal NNS exposure in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with older studies (19), exclusive breastfeeding until 3 months of age was inversely associated with infant WFL z-score; it substantially lowered the risk of child overweight at 1 year in male and especially in female infants. More recently, a study of Asian infants found breastfeeding to be more protective against overweight in male infants (17). Several studies have now linked infant antibiotic use and child overweight, including one by Saari et al that reported an association with overweight development during the first 24 months of life (19).…”
Section: Discussionmentioning
confidence: 99%